Density of Urban Malaria Vector An. stephansi in Parbhani, (M. S.) India - Makne2, Laxmikant V. Shinde1*; Hema (Recent Research in Science and Technology, 2011)
In arthropods mosquito play a vital role as vector of many deadly diseases and Anopheles stephansi is main urban malaria vector parasite in India except North-East region. This paper deals with the density and distribution of An. Stephansi in Parbhani urban. The result shows that the An. Stephansi abundantly found in Sinchan Nagar i. e. 46.28 % and few percent in Pardeshwar Colony (Mandir) locality i. e. 09.25%. Average of An. Stephansi density in Parbhani urban is 27.91% of total anopheline population. Study area also shows very poor awareness about mosquito and mosquito born diseases. These results necessitate further epidemiological surveillance and implicate regular strict monitoring of An. Stephansi in Parbhani to overrule the possibility of An. Stephansi establishment in study area.